Annual trading patterns and risk factors of avian influenza A/H5 and A/H9 virus circulation in turkey birds (Meleagris gallopavo) at live bird markets in Dhaka city, Bangladesh - Islam, Ariful; Amin, Emama; Islam, Shariful; Hossain, Mohammad Enayet; Al Mamun, Abdullah; Sahabuddin, Md.; Samad, Mohammed Abdus; Shirin, Tahmina; Rahman, Mohammed Ziaur; Hassan, Mohammad Mahmudul (Frontiers in Veterinary Science, 2023)
The movement patterns of turkey birds from farms to LBMs and infection with AIV are poorly understood in Bangladesh. Hence, we conducted surveillance in live bird markets (LBMs) to understand the trading patterns, temporal trends, and risk factors of AIV circulation in turkey birds. We sampled turkey birds weekly in two live bird markets (LBMs) in Dhaka between May 2018 and September 2019. We tested the swab samples for the AIV matrix gene (M gene), followed by H5, H7, and H9 subtypes using real-time reverse transcriptase-polymerase chain reaction (rRT-PCR). We used exploratory analysis to investigate trading patterns, trends of AIV and used a generalized estimating equation (GEE) logistic model to identify the factors that influence the infection of A/H5 and A/H9 in turkeys. The number of trades from the source district to Dhaka depends on the turkey density (r = 0.561, P-value = 0.07). The median distance that turkeys were traded from their source district to Dhaka was 188 km (Q1 = 165, Q3 = 210, IQR = 45.5). We observed seasonal variation in the median and average distances of turkeys. The circulation of AIV and A/H9 across the annual cycle showed no seasonality, whereas the circulation of A/H5 showed significant seasonality. The GEE revealed that detection of AIV increases in retail vendor business (OR: 1.71; 95% CI: 1.12–2.62) and the bird's health status is sick (OR: 10.77; 95% CI: 4.31-26.94) or dead (OR: 11.33; 95% CI: 4.30-29.89). We also observed winter season (Odds: 5.83; 95% CI: 2.80–12.14) compared to the summer season, dead birds (Odds: 61.71; 95% CI: 25.78–147.75) and sick birds (Odds: 8.33; 95% CI: 3.36 –20.64) compared to healthy birds has a higher risk of A/H5 infection in turkeys. This study revealed that turkey birds' movements vary by time and season from the farm to the LBM. This surveillance indicated year-round circulation of AIV with H5 and H9 subtypes in turkey birds in LBMs. The seasonality and health condition of birds influence A/H5 infection in birds. The trading pattern of turkey may play a role in the transmission of AIV viruses in the birds.